Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Join our Q&A platform to connect with experts dedicated to providing precise answers to your questions in different areas. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Let's analyze the functions [tex]\( f(x) = 2^x \)[/tex] and [tex]\( g(x) = \left( \frac{1}{2} \right)^x \)[/tex] by looking at the values given in the table:
[tex]\[ \begin{array}{|c|c|c|} \hline x & f(x) = 2^x & g(x) = \left( \frac{1}{2} \right)^x \\ \hline 2 & 4 & \frac{1}{4} \\ \hline 1 & 2 & \frac{1}{2} \\ \hline 0 & 1 & 1 \\ \hline -1 & \frac{1}{2} & 2 \\ \hline -2 & \frac{1}{4} & 4 \\ \hline \end{array} \][/tex]
Now, let's compare the values of [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex]:
1. For [tex]\( x = 2 \)[/tex]:
[tex]\[ f(2) = 2^2 = 4, \quad g(2) = \left( \frac{1}{2} \right)^2 = \frac{1}{4} \][/tex]
2. For [tex]\( x = 1 \)[/tex]:
[tex]\[ f(1) = 2^1 = 2, \quad g(1) = \left( \frac{1}{2} \right)^1 = \frac{1}{2} \][/tex]
3. For [tex]\( x = 0 \)[/tex]:
[tex]\[ f(0) = 2^0 = 1, \quad g(0) = \left( \frac{1}{2} \right)^0 = 1 \][/tex]
4. For [tex]\( x = -1 \)[/tex]:
[tex]\[ f(-1) = 2^{-1} = \frac{1}{2}, \quad g(-1) = \left( \frac{1}{2} \right)^{-1} = 2 \][/tex]
5. For [tex]\( x = -2 \)[/tex]:
[tex]\[ f(-2) = 2^{-2} = \frac{1}{4}, \quad g(-2) = \left( \frac{1}{2} \right)^{-2} = 4 \][/tex]
Notice that [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] are related in such a way that [tex]\( f(x) = g(-x) \)[/tex]. This indicates that the values of [tex]\( g(x) \)[/tex] are essentially the values of [tex]\( f(x) \)[/tex] when the signs of [tex]\( x \)[/tex] are flipped. This relationship shows that the functions [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] are reflections of each other over the [tex]\( y \)[/tex]-axis.
Therefore, the correct conclusion about [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] from the table is:
- The functions [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] are reflections over the [tex]\( y \)[/tex]-axis.
[tex]\[ \begin{array}{|c|c|c|} \hline x & f(x) = 2^x & g(x) = \left( \frac{1}{2} \right)^x \\ \hline 2 & 4 & \frac{1}{4} \\ \hline 1 & 2 & \frac{1}{2} \\ \hline 0 & 1 & 1 \\ \hline -1 & \frac{1}{2} & 2 \\ \hline -2 & \frac{1}{4} & 4 \\ \hline \end{array} \][/tex]
Now, let's compare the values of [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex]:
1. For [tex]\( x = 2 \)[/tex]:
[tex]\[ f(2) = 2^2 = 4, \quad g(2) = \left( \frac{1}{2} \right)^2 = \frac{1}{4} \][/tex]
2. For [tex]\( x = 1 \)[/tex]:
[tex]\[ f(1) = 2^1 = 2, \quad g(1) = \left( \frac{1}{2} \right)^1 = \frac{1}{2} \][/tex]
3. For [tex]\( x = 0 \)[/tex]:
[tex]\[ f(0) = 2^0 = 1, \quad g(0) = \left( \frac{1}{2} \right)^0 = 1 \][/tex]
4. For [tex]\( x = -1 \)[/tex]:
[tex]\[ f(-1) = 2^{-1} = \frac{1}{2}, \quad g(-1) = \left( \frac{1}{2} \right)^{-1} = 2 \][/tex]
5. For [tex]\( x = -2 \)[/tex]:
[tex]\[ f(-2) = 2^{-2} = \frac{1}{4}, \quad g(-2) = \left( \frac{1}{2} \right)^{-2} = 4 \][/tex]
Notice that [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] are related in such a way that [tex]\( f(x) = g(-x) \)[/tex]. This indicates that the values of [tex]\( g(x) \)[/tex] are essentially the values of [tex]\( f(x) \)[/tex] when the signs of [tex]\( x \)[/tex] are flipped. This relationship shows that the functions [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] are reflections of each other over the [tex]\( y \)[/tex]-axis.
Therefore, the correct conclusion about [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] from the table is:
- The functions [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] are reflections over the [tex]\( y \)[/tex]-axis.
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.